Fractions


  1. ( 0.5 x 0.5 x 0.5 x 0.6 x 0.6 x 0.6 ) / ( 0.5 x 0.5 - 0.3 + 0.6 x 0.6 ) = ?
    1. 0.3
    2. 1.1
    3. 0.1
    4. 0.61

  1. View Hint View Answer Discuss in Forum

    Given expression
    = [(0.5)3 + (0.6)3 ] / [(0.5)2 - 0.5 x 0.6 + (0.6)2]
    = (a3+b3) / ( a2-ab+b2)
    = a + b
    = 0.5 + 0.6

    Correct Option: B

    Given expression
    = [(0.5)3 + (0.6)3 ] / [(0.5)2 - 0.5 x 0.6 + (0.6)2]
    = (a3+b3) / ( a2-ab+b2)
    = a + b
    = 0.5 + 0.6
    = 1.1


  1. (.125 + .027) / (.5 x .5 - 1.5 + .09) = ?
    1. .08
    2. 1
    3. .2
    4. .8

  1. View Hint View Answer Discuss in Forum

    Given expression
    = [(0.5)3 + (0.3)3] / [(0.5)2 - 0.5 x 0.3 + (0.3)2]
    = [a3 + b3] / [a2 - ab + b2]
    = [(a + b)(a2 - ab + b2)] / [a2 -ab + b2]
    = a+b
    = 0.5 + 0.3

    Correct Option: D

    Given expression
    = [(0.5)3 + (0.3)3] / [(0.5)2 - 0.5 x 0.3 + (0.3)2]
    = [a3 + b3] / [a2 - ab + b2]
    = [(a + b)(a2 - ab + b2)] / [a2 -ab + b2]
    = a+b
    = 0.5 + 0.3
    = 0.8



  1. (0.47 x 0.47 x 0.47 - 0.33 x 0.33 x 0.33) / (0.47 x 0.47 + 0.47 x 0.33 + 0.33 x 0.33) = ?
    1. 0.14
    2. 0.8
    3. 15.51
    4. 1

  1. View Hint View Answer Discuss in Forum

    Given expression
    = [(0.47)3 - (0.33)3] / [(0.47)2 + 0.47 x 0.33 + (0.33)2]
    = [a3 - b3 ] / [ a2 + ab + b2]
    = [(a-b) (a2 + ab + b2)] / [(a2 + ab + b2)]
    = (a - b)
    = (0.47 - 0.33)

    Correct Option: A

    Given expression
    = [(0.47)3 - (0.33)3] / [(0.47)2 + 0.47 x 0.33 + (0.33)2]
    = [a3 - b3 ] / [ a2 + ab + b2]
    = [(a-b) (a2 + ab + b2)] / [(a2 + ab + b2)]
    = (a - b)
    = (0.47 - 0.33)
    = 0.14


  1. (1.04 x 1.04 + 1.04 x 0.04 + 0.04 x 0.04) / (1.04 x 1.04 x 1.04 - 0.04 x 0.04 x 0.04) = ?
    1. 0.10
    2. 0.1
    3. 1
    4. 0.01

  1. View Hint View Answer Discuss in Forum

    Given Expression = (1.04)2 + 1.04 x 0.04 + (0.04)2 / (1.04)3 - (0.04)3
    = (a2 + ab + b2) / (a3 - b3)
    = (a2 + ab + b2) / [(a-b) (a2 + ab + b2)]
    = 1 / (a - b)
    = 1/ (1.04 - 0.04)

    Correct Option: C

    Given Expression = (1.04)2 + 1.04 x 0.04 + (0.04)2 / (1.04)3 - (0.04)3
    = (a2 + ab + b2) / (a3 - b3)
    = (a2 + ab + b2) / [(a-b) (a2 + ab + b2)]
    = 1 / (a - b)
    = 1/ (1.04 - 0.04)
    = 1



  1. [(0.87)3 + (0.13)3] / [(0.87)2 - 0.87 x 0.13 + (0.13)2] = ?
    1. 0.13
    2. 0.74
    3. 0.87
    4. 1

  1. View Hint View Answer Discuss in Forum

    Given Expression = ( a3 + b3 )/ (a2 + b2 - ab) where = 0.87 and b = 0.13
    = [(a + b ) (a2 + b2 - ab)] / (a2 + b2 - ab)
    = a + b
    = 0.87 + 0.13

    Correct Option: D

    Given Expression = ( a3 + b3 )/ (a2 + b2 - ab) where = 0.87 and b = 0.13
    = [(a + b ) (a2 + b2 - ab)] / (a2 + b2 - ab)
    = a + b
    = 0.87 + 0.13
    = 1